Family Health Friday Civitas Akademika Kampus IBI Kosgoro 1957 dan Warga Masyarakat Kecamatan Jagakarsa - Filda Angellia; Boy Firmansyah (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
Technology which is currently developing rapidly requires and guides human life to be more advanced. But technology can also sometimes be a